Aztec Religion and Art of Writing : Investigating Embodied Meaning, Indigenous Semiotics, and the Nahua Sense of Reality - Laack, Isabel. (Numen Book Series, 2019)
In her groundbreaking investigation from the perspective of the aesthetics of religion, Isabel Laack explores the religion and art of writing of the pre-Hispanic Aztecs of Mexico. Inspired by postcolonial approaches, she reveals Eurocentric biases in academic representations of Aztec cosmovision, ontology, epistemology, ritual, aesthetics, and the writing system to provide a powerful interpretation of the Nahua sense of reality. Laack transcends the concept of "sacred scripture" traditionally employed in religions studies in order to reconstruct the Indigenous semiotic theory and to reveal how Aztec pictography can express complex aspects of embodied meaning. Her study offers an innovative approach to nonphonographic semiotic systems, as created in many world cultures, and expands our understanding of human recorded visual communication. This book will be essential reading for scholars and readers interested in the history of religions, Mesoamerican studies, and the ancient civilizations of the Americas. 'This excellent book, written with intellectual courage and critical self-awareness, is a brilliant, multilayered thought experiment into the images and stories that made up the Nahua sense of reality as woven into their sensational ritual performances and colorful symbolic writing system.' - Davíd Carrasco, Harvard University